2016
DOI: 10.1371/journal.pone.0165461
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low-Dose Ketamine on Acute Pain in an Emergency Setting: A Systematic Review and Meta-Analysis

Abstract: ObjectivesCurrently ketamine is not used often as an analgesic in the emergency department (ED). Nonetheless, it can increase the efficiency of opioids and decrease their side effects. The purpose of this systematic review and meta-analysis was to evaluate whether low-dose ketamine in the ED provides better analgesia with fewer adverse effects.MethodsThe PubMed, EMBASE, and Cochrane Library databases were searched by two reviewers independently (last search performed on January 2016). Data were also extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 50 publications
(84 reference statements)
1
59
0
2
Order By: Relevance
“…Of the four studies included, two showed a benefit in pain and distress with ketamine, while the others demonstrated either no difference between ketamine and fentanyl or ketamine and a placebo. In another meta‐analysis that also included trials we excluded, Lee and Lee included six trials and 438 patients and found ketamine to be either similar or superior to opioids and placebos. Ketamine was associated with a higher rate of neurologic and psychiatric adverse events (respectively, RR = 2.17, 95% CI = 1.37 to 3.42, p < 0.001, NNH = 9; RR = 13.86, 95% CI = 4.85 to 39.58, p < 0.001, NNH = 4), while opioids were associated with a higher risk of major cardiovascular events (RR = 0.22, 95% CI = 0.05–1.01, p = 0.05, NNH = 28), although the clinical significance of this is debatable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the four studies included, two showed a benefit in pain and distress with ketamine, while the others demonstrated either no difference between ketamine and fentanyl or ketamine and a placebo. In another meta‐analysis that also included trials we excluded, Lee and Lee included six trials and 438 patients and found ketamine to be either similar or superior to opioids and placebos. Ketamine was associated with a higher rate of neurologic and psychiatric adverse events (respectively, RR = 2.17, 95% CI = 1.37 to 3.42, p < 0.001, NNH = 9; RR = 13.86, 95% CI = 4.85 to 39.58, p < 0.001, NNH = 4), while opioids were associated with a higher risk of major cardiovascular events (RR = 0.22, 95% CI = 0.05–1.01, p = 0.05, NNH = 28), although the clinical significance of this is debatable.…”
Section: Discussionmentioning
confidence: 99%
“…As patients can still become dissociated or have psychiatric complaints, we shall instead refer to this as low‐dose ketamine (LDK). Two previously conducted reviews evaluating LDK in the ED suffered significant limitations by including pediatric trials, trials where ketamine was administered with other analgesics, and patients where ketamine was administered for procedural sedation leaving the independent effect of ketamine on acute pain control unresolved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If low dose ketamine is used in the emergency department as a pharmacological treatment for pain, it is important to take into consideration the risks and benefits, least effective and most effective uses. Low dose ketamine is an effective pharmacological treatment of pain by itself and as an adjunct to opioids [7] [30] because it is a non-competitive NMDA antagonist and it does not interfere with receptors used by opioids [7] [19] [30]. As an adjunct therapy, it is especially important to consider the dosing of opioids in order to prevent opioid-ketamine adverse reactions.…”
Section: Considerations For Practitioners and Nursesmentioning
confidence: 99%
“…However, in recent years, an increased desire for alternatives has been prompted in an attempt to reduce opiate usage . Several studies have been performed evaluating low‐dose ketamine (LDK) for acute pain, with a variety of methodologic designs, time endpoints, and doses . This review attempts to determine the utility of LDK, alone, in comparison to opiates for acute pain in the ED.…”
Section: Introductionmentioning
confidence: 99%